The dangerous book: observations on the prose by Danilo Kiš, Aleksandar Hemon and Igor Štiks (Colloquia Comparativa Litterarum, 2025)
The text compares three books by South Slavic authors: A Tomb for Boris Davidovic (1976) by Danilo Kiš, The Lazarus Project (2008) by Aleksandar Hemon, and Elijah’s Chair by Igor Štiks. In different genres, all three books analyse possibilities to defend human rights, and particularly the freedom of speech and thought. In these literary worlds, Europe exists mainly with its philosophical and cultural history, but also as a place with a very long tradition both in the defence and in violation of human freedom. Of course, the book as a main symbol of wisdom and thought is the primary subject of these works, and therefore it is not surprising that their writers devote important space to ‘dangerous books’ and knowledge, and ask about ethic and poetic borders between permission and prohibition.
Keywords: Balkan cultures and literatures; Jewish culture; urban culture; comparative literature